PENGARUH BERBAGAI FREKUENSI PEMBERIPENGARUH BERBAGAI FREKUENSI PEMBERIAN PAKAN DAN PEMBATASAN PAKAN TERHADAP EFISIENSI PENGGUNAAN PROTEIN AYAM BROILER - Iqbal, Fahim; Atmomarsono, Umiyati; Muryani, Rina (Animal Agriculture Journal, 2012)
The research was aims to determine the influence of various feeding frequency and feed restriction on protein utilization of broiler chicken which includes the consumption of protein, protein efficiency ratio and nitrogen retention The experiment used 200 days old chick broilers unsex. Feed rations were calculated 22,69% crude protein; 2930 kcal/kg metabolizable energy. Completely Randomized Design with 4 treatments and 5 replication was used in this experiment. Feed provided ad libitum at the age of 1-7 days. feed restriction (75% standard) with frequency of 8-21 days with treatment at T0 = ad libitum-feed; T1 = 4 times given at 06.00, 10.00, 14.00 and 18.00, T2 = 3 times gave at 06.00, 14.00 and 18.00, T3 = 2 times were gave at 06.00 and 14.00. Feed provided ad libitum at the age of 22-35 days. The results showed that the influence of feeding frequency and feed restriction no significant effect (P> 0.05) on protein consumption, protein efficiency ratio and nitrogen retentionKey words: feed restriction, consumption of protein, protein efficiency ratio, nitrogen retention, broiler chicken